Workload, Work-life Balance, and Their Effects on Employees’ Turnover Intention in Convection Industry - Pangestuti, Yunia Safrida; Al Karim, Chamilul Hikam (Dinasti Publisher, 2025)
The convection industry, as a labor-intensive sector, faces high turnover risk influenced by work pressure and work-life imbalance, but studies on the relationship between these two factors are still limited to the context of medium-scale garment manufacturing. This study analyzes how workload and work-life balance affect the likelihood of employees at CV X leaving their jobs. The study uses a correlational quantitative approach with a sample of 118 employees selected through simple random sampling. The instruments used include the NASA-TLX scale to measure workload, the work-life balance scale, and Mobley's turnover intention scale. Data analysis was performed using multiple linear regression after all statistical assumptions were met. The findings show that workload has a positive and significant impact on the desire to leave a job, but work-life balance does not have a strong influence. However, when both factors are considered together, they have a significant influence on the intention to leave a job. These findings confirm that high work demands are a major factor driving increased turnover intention, while work-life balance is not a direct determinant for blue-collar workers with an WFO system. The implications of this study underscore the need for proportional workload management and work recovery strategies to reduce turnover in the convection industry.